2020
DOI: 10.21203/rs.2.18964/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus nasal colonization among HIV-infected patients in Taiwan: prevalence, molecular characteristics and associated factors with nasal carriage

Abstract: Background: To evaluate nasal carriage, antibiotic susceptibility and molecular characteristics of methicillin-resistant Staphylococcus aureus (MRSA), as well as the risk factors of MRSA colonization, in human immunodeficiency virus (HIV)-infected patients in northern Taiwan.Methods: From September 2014 to November 2015, HIV-infected patients seeking outpatient care at four hospitals were eligible for this study. A nasal specimen was obtained from each subject for the detection of S. aureus and a questionnair… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…A total of 31 studies, representing a total of 17 427 patients with HIV infection, were selected for the final meta-analysis. 2656 The details of the literature search and study selection are summarized in a PRISMA flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 31 studies, representing a total of 17 427 patients with HIV infection, were selected for the final meta-analysis. 2656 The details of the literature search and study selection are summarized in a PRISMA flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the included studies and recruited patients are presented in Table 1. 2656 Of the 31 included studies, eight had a cohort design, 17 had a cross-sectional design and the remaining six studies had a case–control design. These studies reported a total of 1410 MRSA colonization events and the events of MRSA colonization and infection that occurred in each study ranged from 6 to 252.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations